Impact of Urban-Rural Integrated Development on Carbon Emission Intensity of Land Use: A Case Study of the Changsha–Zhuzhou–Xiangtan Urban Agglomeration - Li Xiaoqing; Zhou Guohua; Cui Shuqiang; Wang Hua; Liu Hui; Yu Xuexia (Redai dili)
Against the backdrop of intensifying global climate change, an international consensus has been reached on the realization of the "dual carbon" goal. By optimizing resource allocation and also strengthening ecological protection, integrated urban-rural development has a significant effect on curbing land-use carbon emission intensity, while promoting high-quality economic and social development. In this study, we built an analytical framework for the impact of urban-rural integration on land-use carbon emission intensity by considering the carbon reduction effect and carbon increase effect generated by urban-rural integration. It has also empirically examined the impact of urban-rural integration on land-use carbon emission intensity and spatial spillover effects based on the panel data of 22 counties in the Changsha–Zhuzhou–Xiangtan urban agglomeration between 2005 and 2021 using the spatial Durbin model. We found that 1) urban-rural integration accelerates the circulation of human, capital, technology, and other factors in urban and rural production and living activities, which affect the pattern and function of regional carbon sources and sinks by improving land-use efficiency, optimizing land allocation, and increasing energy consumption. This generated a carbon reduction effect and carbon increase effect and brought about a change in the intensity of land-use carbon emissions as a result of the economic output of the region. 2) From 2005 to 2021, the urban-rural integrated development of the Changsha–Zhuzhou–Xiangtan urban agglomeration demonstrated an overall upward trend, and its process is embodied in the three-tier coordinated advancement of "overall–municipal–county." From the urban agglomeration overall and municipal level perspectives, the urban-rural integrated development level showed a continuous upward trend; from the county level perspective, it generally exhibited a spatial evolution pattern decreasing from central urban areas to surrounding counties and has a convergence trend. 3) From 2005 to 2021, the land-use carbon emission intensity at the urban agglomeration overall, municipal, and county levels showed an overall annual decreasing trend. At the time series level, during the study period, the intensity of the land-use carbon emission intensity of Changsha was always higher than that of Zhuzhou and Xiangtan, but the gap between the three cities continued to narrow. At the level of the spatial evolution in the counties, the spatial distribution characteristics of high in the northeast and low in the northwest and southwest showed distribution characteristics. 4) Spatial Durbin results show that urban-rural integration demonstrated significant negative inhibitory effects at the levels of direct, indirect, and total effects, thus, indicating that urban-rural integrated development could significantly reduce the land-use carbon emission intensity. The increase in population density and proportion of secondary industry have positive effects on land-use carbon emission intensity, while government behavior, technological level, and openness level have negative effects on land-use carbon emission intensity. This study not only provides new research perspectives for in-depth analysis of urban–rural integration and carbon emission intensity of land use but also provides reference for exploring new paths of urban–rural green and low-carbon development and realizing the goal of "dual carbon."